A branching-time logic to verify synchronously coupled concurrent systems and its relevance to web-based systems. (2015) - Narayanan, Vasumathi K.; Dakshinamurthy, Sungeetha
This paper is a sequel to our previous work wherein we proposed a state-based partial-order concurrency model from a given specification of communicating finite state machines (CFSMs), constituting a cooperative system specification. We unfold the CFSMs by simulating them in global environment to generate what we proposed as communicating minimal prefix machines (CMPMs). In this present work, we proceed from the unfolded CMPMs and go on to show that they form a distributed set of concurrent Kripke tree structures, over which we propose the logic computational distributed tree logic (CDTL) for model-checking. We show that CDTL provides an interesting set of expressive and nested formulae to verify safety, liveness and fairness properties. The component Kripke structures keep track of their respective local identities and at the same time maintain a global view through the environment vectors annotating every local CMPM state of the component Kripke structure. As a result, we achieve modularity as well as alleviation of state-explosion in our model-checking. Application of model-checking on web-systems is discussed.